2006
DOI: 10.2135/cropsci2006.04.0227
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Approach for Assessing the Stability of Genotypes

Abstract: Several statistical models can be used for assessing genotype 3 environment interaction (GEI) and studying genotypic stability. The objectives of this research were to show how (i) to use Bayesian methodology for computing Shukla's phenotypic stability variance and (ii) to incorporate prior information on the parameters for better estimation. Potato [Solanum tuberosum subsp. andigenum (Juz. & Bukasov) Hawkes], wheat (Triticum aestivum L.), and maize (Zea mays L.) multi environment trials (MET) were used for il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
2
25
0
2
Order By: Relevance
“…Significant GEI suggest a linier function of the additive environment effects, and was reflected by the change in the ranking order of genotypes under varying environments. Similar results were reported by earlier authors (Amin et al, 2005;Ali, 2006;Cotes et al, 2006). However, the overall performance of the genotypes depends upon the magnitude of GEI.…”
Section: Resultssupporting
confidence: 91%
“…Significant GEI suggest a linier function of the additive environment effects, and was reflected by the change in the ranking order of genotypes under varying environments. Similar results were reported by earlier authors (Amin et al, 2005;Ali, 2006;Cotes et al, 2006). However, the overall performance of the genotypes depends upon the magnitude of GEI.…”
Section: Resultssupporting
confidence: 91%
“…This approach uses three basic concepts: initial information (a priori probability), generally assumed as a joint probability law on the parameters before obtaining the private information of the samples y 1 , ..., y n of the random variable; the probabilistic model of random response variable y, with which it obtains the likelihood of the sample; and Bayes' theorem, which combines the a priori information and the likelihood function and generates a posterior distribution (Cotes et al, 2006;Silva et al, 2013). Nascimento et al (2011) formulated a Bayesian approach using the Eberhart and Russell (1966) method to evaluate GE interaction, and concluded that the selection of genotypes in different environments was most accurate when a priori information was used.…”
Section: Introductionmentioning
confidence: 99%
“…Nascimento et al (2011) formularam uma abordagem bayesiana para o método de Eberhart & Russel (1966), que permitiu maior acurácia na seleção de genótipos de alface, em comparação ao método tradicional. Esta abordagem utiliza três conceitos básicos: uma informação inicial (probabilidade a priori), geralmente assumida como uma lei de probabilidade conjunta sobre os parâmetros, antes de se obter a informação particular das amostras y 1 ,...,y n da variável aleatória; o modelo probabilístico da variável aleatória resposta y, com o qual se obtém a verossimilhança da amostra; e o teorema de Bayes, que combina a informação a priori e a função de verossimilhança, e gera uma distribuição a posteriori (Cotes et al, 2006). Assim, no contexto bayesiano, os parâmetros passam a ser interpretados como variáveis aleatórias, com uma lei de probabilidade (distribuição a priori) que reflete uma informação inicial (ou a falta de informação) sobre eles, independentemente do que os dados possam mostrar (Ramos Molina et al, 2012).…”
Section: Introductionunclassified
“…Assim, no contexto bayesiano, os parâmetros passam a ser interpretados como variáveis aleatórias, com uma lei de probabilidade (distribuição a priori) que reflete uma informação inicial (ou a falta de informação) sobre eles, independentemente do que os dados possam mostrar (Ramos Molina et al, 2012). Outra peculiaridade dessa análise é que a homogeneidade da variância e a adequação dos resíduos à distribuição normal, pressupostos para muitas metodologias, não são requeridos na abordagem bayesiana (Cotes et al, 2006). Embora a inferência bayesiana seja um procedimento estatístico robusto e tenha muitas aplicações possíveis, sua utilização no melhoramento genético de plantas ainda é pequena.…”
Section: Introductionunclassified